Answers

2015-10-31T22:50:02+05:30
For question no. 35 answer is (A)

Just use the identity

a³-b³ = (a-b)(a²+b²+ab)

(2x)³-(3y)³ = (2x-3y)(4x²+9y²-6xy)

For question no.38 correct answer is (c)

using ,

(a+b)² = a²+b²+2ab

a²+b² = (a+b)²-2ab

using this

(x²)² + (2)²

(x²+2)² - 4x²

(x²+2)² - (2x)²

(x²+2x+2)(x²-2x+2)
0
2015-11-01T15:00:44+05:30
For question no. 35 answer is (A) 

Just use the identity 

a³-b³ = (a-b)(a²+b²+ab)

(2x)³-(3y)³ = (2x-3y)(4x²+9y²-6xy)

For question no.38 correct answer is (c)

using ,

(a+b)² = a²+b²+2ab

a²+b² = (a+b)²-2ab

using this 

(x²)² + (2)²

(x²+2)² - 4x²

(x²+2)² - (2x)²

(x²+2x+2)(x²-2x+2)
0